Pengaruh Program Dana Desa Terhadap Peningkatan Infrastruktur Dan Kesejahteraan Sosial di Desa - Tino Supriantino; Wahyu; Tardi Setiabudi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study investigates the impact of the Village Fund Program on the improvement of social welfare and village infrastructure. The challenges faced in the management of the Village Fund, such as transparency and community participation. To demonstrate that Village Funds can improve the quality of life for the community through infrastructure development and economic empowerment, the literature review collects data from various relevant sources. The research results show that the allocation of Village Funds improves infrastructure, such as roads and public facilities, and enhances access to basic services for the community. Village Fund also has a positive impact on the economic, social, and health aspects of the village community. This research found that the Village Fund program heavily relies on good management, active community participation, and support from the local government. Therefore, it is necessary to enhance transparency, accountability, and training for village officials to maximize the benefits that the community can obtain from the Village Fund.